1993
DOI: 10.1590/s0103-90161993000300026
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças periódicas dos ingredientes alimentares associadas às diferentes formas de ração no desempenho de frangos de corte

Abstract: Efeitos da forma de ração (triturada e farelada), sexos e mudanças semanais na composição centesimal das rações no peso corporal, ganho de peso e conversão alimentar de frangos de corte no período de 1 até 49 dias de idade, foram testados através de delineamento fatorial 2 x 2 x 2, com 3 repetições de 50 aves cada. A ração basal foi formulada para conter milho moído, farelo de soja, fosfato bicálcico, calcáreo, gordura animal, sal e suplemento de vitaminas, minerais e aditivos. As mudanças na composição foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The similarity of AME, AMEn and CMDM values between diets with or without an abrupt change of grains shows that this change did not impair the metabolizability of diets. In contrast, another study demonstrated an increase in body weight and weight gain in broilers fed diets with periodical ingredient changes; however, in that study, the metabolizability of the diets was not evaluated (Miltenburg et al., ).…”
Section: Resultsmentioning
confidence: 92%
“…The similarity of AME, AMEn and CMDM values between diets with or without an abrupt change of grains shows that this change did not impair the metabolizability of diets. In contrast, another study demonstrated an increase in body weight and weight gain in broilers fed diets with periodical ingredient changes; however, in that study, the metabolizability of the diets was not evaluated (Miltenburg et al., ).…”
Section: Resultsmentioning
confidence: 92%